2015
DOI: 10.4018/ij3dim.2015100101
|View full text |Cite
|
Sign up to set email alerts
|

3D Web Services for Visualization and Data Sharing in 3D Cadastre

Abstract: Land has an essential role in any society, either as one of the most important capitals of mankind or as a place for people's life and activities. Therefore, registration of ownership and land use rights in a formal system is a major issue. In different countries, Cadastre systems can register extent, rights, restrictions and responsibilities related to land parcels. Many organizations such as municipality, tax and banks need to this information for planning and decision making. Considering the needs for land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The LADM focuses on the areas of land administration that are mainly connected to real properties, land ownership and the geometrical (spatial) components of natural resources [31]. This model provides a framework to extend property models to fit different administrative systems.…”
Section: Construction Of An Nrum Modelmentioning
confidence: 99%
“…The LADM focuses on the areas of land administration that are mainly connected to real properties, land ownership and the geometrical (spatial) components of natural resources [31]. This model provides a framework to extend property models to fit different administrative systems.…”
Section: Construction Of An Nrum Modelmentioning
confidence: 99%
“…The authors provided a visualisation using 3D buildings to show the calculated energy demand of each building. Zardiny and Hakimpour (2015) indicated that 3D Spatial Web Services allow on the fly construction and on demand presentation of the 3D cadastral models via Web.3D representations of city objects, which can be populated from 2D, or 3D vector models. 3D representations of city objects can also be generated (reconstructed) using images.…”
Section: Visualisation Of 3d and Time-varying Geo-informationmentioning
confidence: 99%